Up‐regulation of circulating miR‐20a is correlated with hepatitis C virus‐mediated liver disease progression12. Issue 3 (23rd July 2013) - Shrivastava, Shubham; Petrone, Jessica; Steele, Robert; Lauer, Georg M.; Di, Adrian M.; Ray, Ratna B.
<x xml:space="preserve">Abstract</x> Chronic hepatitis C virus (HCV) infection is one of the major causes of liver fibrosis and liver transplantation in the United States. Circulating microRNAs (miRNAs) in the blood are emerging as biomarkers for pathological conditions. In the present study we performed a systematic screening approach to identify up‐regulated miRNAs in the plasma/serum of HCV‐infected patients with different stages of hepatic histological disease severity. We initially screened serum samples of HCV‐infected patients with fibrosis and compared them with sera of healthy volunteers using serum miRNA array profiling and identified a group of modulated miRNAs. Subsequent study demonstrated that miR‐20a and miR‐92a in HCV‐infected fibrosis patients sera were significantly up‐regulated when compared with that of healthy volunteers or non‐HCV‐associated liver disease. We have also observed an increase of plasma miR‐20a and miR‐92a in acute and chronic HCV‐infected patients as compared to that of healthy volunteers. However, there was no correlation between the plasma/serum levels of any of these miRNAs with HCV viral loads. We next investigated longitudinal plasma samples from HCV‐infected patients. Our results suggested that miR‐20a and miR‐92a remained unaltered in HCV‐infected patients who progressed from acute to chronic infection. On the other hand, miR‐92a expression was reduced in acute to resolved individuals. These data provide evidence that plasma/serum levels of miR‐20a and miR‐92a have potential as sensitive and cost‐effective biomarkers for early detection of HCV infection. Conclusion: Circulating miR‐20a may serve as a potential for predictive biomarker in HCV‐mediated fibrosis. (Hepatology 2013;53:863–871)